The Comparison of Effects of Gamma Radiation of Crude Oil Yield on Some Sunflower (Helianthus annuus) Seeds - Havser ERTEM VAİZOĞULLAR (International Journal of Secondary Metabolite, 2016)
This study compares the effects of different doses gamma radiation on crude oil yield and moisture of different six variety sunflower (Helianthus annuus L.) seeds. As materials, sunflower variety Ege-2001, Turay, AS-508, Tunca, TR-3080 and Tarsan-1018 seeds were used and irradiated with doses of 0 (control), 100, 200, 300, 400 and 500 Gy gamma radiation. Irradiation was performed in a cesium (Ce137) Gammacell 3000 Elan source, dose rate about 9.75 Gy/min (2900 Ci) in the Pamukkale University Faculty of Medicine in the department of the radiological. Moisture amount of seeds were also measured by AOCS standarts. Extraction of the seeds was done with soxhlet apparatus using petroleum ether by hot continuous extraction for 6 hours. It was found that the highest moisture rate in 100 Gy for all seeds variety. The moisture rate ranged between 3.00 and 9.68% in TR-3080 and Ege-2001, respectively. According to the our results, seed moisture content was affected by gamma radiation in a significant negative one-way. The significant reduction in seed moisture content (9.68%) began at 100 Gy of gamma rays and continued to decline to up to 4.04% at 500 Gy. The crude oil yield showed not a important increase in 100 and 200 Gy doses. The result showed that the highest crude oil yield was also obtained from 400 Gy and 33.49% in Ege-2001 seeds.